Novel environment-friendly fracturing fluid and preparation method thereof

By using modified nanocellulose-montmorillonite composite powder in the fracturing fluid, a stable three-dimensional network structure is formed, which solves the shortcomings of traditional fracturing fluid in terms of bubble formation, bubble stabilization, sand carrying and environmental protection, and achieves efficient and environmentally friendly fracturing fluid performance.

CN119875609AActive Publication Date: 2025-04-25XIAN KAIERWEN PETROCHEMICAL AUXILIARY MFG CO LTD

Patent Information

Application Number
CN202510377288.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

Traditional fracturing fluid has shortcomings in bubble efficiency, bubble stabilization ability, sand carrying performance and environmental protection, resulting in poor crack support effect, affecting oil and gas extraction efficiency, and posing a potential environmental pollution risk.

Method used

Modified nanocellulose-montmorillonite composite powder is used as the main component, and a stable three-dimensional network structure is formed through specific modification and composite treatment, which improves the foaming, bubble stabilization and sand carrying properties of the fracturing fluid, and reduces environmental pollution through deionized water and environmentally friendly raw materials.

Benefits of technology

It significantly improves the foaming efficiency and bubble stabilization ability of the fracturing fluid, ensures that it can play a stable role under different temperatures and reservoir conditions, improves sand carrying performance and environmental protection, and reduces mining costs and environmental pollution risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875609A_ABST
    Figure CN119875609A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fracturing fluids, in particular to a novel environment-friendly fracturing fluid and a preparation method thereof. The fracturing fluid is prepared from the following components in parts by weight: 90 to 95 parts of deionized water, 1 to 3 parts of modified nano cellulose-montmorillonite composite powder, 0.1 to 0.3 part of a foaming agent, 0.2 to 0.8 part of a thickening agent and 0.5 to 1.5 parts of a cross-linking agent. The modified nanocellulose-montmorillonite composite powder is prepared by activating carboxylated nanocellulose, crosslinking the activated carboxylated nanocellulose with carboxylic acid-polyethylene glycol-carboxylic acid and triethylene tetramine, and compounding and intercalating modified montmorillonite. The prepared novel environment-friendly fracturing fluid has good foaming capacity, excellent sand-carrying capacity and good stability at different temperatures, the raw materials are environmentally friendly, the pollution risk to the environment is reduced, the novel environment-friendly fracturing fluid is suitable for fracturing construction under various reservoir conditions, and the oil and gas exploitation efficiency can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fracturing fluid, and in particular to a novel environmentally friendly fracturing fluid and a preparation method thereof. Background Art

[0002] In the field of oil and gas extraction, fracturing fluid technology is crucial, and its performance is directly related to extraction efficiency and cost. Traditional fracturing fluids have many drawbacks, which seriously restrict the development of the industry. Some traditional fracturing fluids have low foaming efficiency, and it is difficult to form a large amount of stable foam during the construction process. They cannot effectively carry proppants into the formation cracks, resulting in poor crack support effect, affecting the smooth extraction and transmission of oil and gas. At the same time, their foam stabilization ability is poor, the foam half-life is short, it is easy to break, and it is difficult to maintain the open state of the cracks, which reduces the extraction efficiency. In terms of sand carrying performance, traditional fracturing fluids also perform poorly and cannot effectively prevent the proppant from settling, resulting in uneven distribution of proppants, affecting the improvement of formation permeability, and thus reducing oil and gas production.

[0003] In addition, with increasingly stringent environmental protection requirements, the composition of traditional fracturing fluids may be unfriendly to the environment and pose potential pollution risks. It is urgent to develop a new fracturing fluid with high foaming efficiency, strong foam stabilization ability, excellent sand carrying performance, suitable gel breaking time and environmental protection, which is of great significance to improving oil and gas production efficiency, reducing costs and protecting the environment. Summary of the invention

[0004] In view of this, the purpose of the present invention is to propose a new environmentally friendly fracturing fluid and a preparation method thereof, so as to solve the problems of the existing traditional fracturing fluid, such as weak sand carrying capacity, short foam half-life, and poor foam stabilization ability at high temperature.

[0005] Based on the above purpose, the present invention provides a new environmentally friendly fracturing fluid, characterized in that it comprises the following raw materials in parts by weight: deionized water: 90-95 parts, modified nanocellulose-montmorillonite composite powder: 1-3 parts, foaming agent: 0.1-0.3 parts, thickener: 0.2-0.8 parts, cross-linking agent: 0.5-1.5 parts; The specific preparation method of the modified nanocellulose-montmorillonite composite powder is as follows: The carboxylated nanocellulose and carboxylic acid-polyethylene glycol-carboxylic acid are co-dispersed in an activation solution, subjected to ultrasonic treatment for 1-3 hours, and then triethylenetetramine is added. Under nitrogen protection, the mixture is stirred at 55-65°C for 5-7 hours, and then freeze-dried, washed with n-hexane, and dried to obtain modified nanocellulose. Mix montmorillonite, hexadecyltrimethylammonium bromide and deionized water, keep stirring at 50-70°C for 1-3 hours, filter, wash and dry to obtain intercalated modified montmorillonite; The intercalated modified montmorillonite in (2) is added to deionized water, heated to 60-80°C and stirred for 2-4 hours, and then the modified nanocellulose obtained in (1) is added, ultrasonicated for 20-30 minutes, and then stirred for 6-12 hours. After cooling to room temperature, freeze-drying, grinding through a 1000-1500 mesh sieve, and obtaining a modified nanocellulose-montmorillonite composite powder.

[0006] Preferably, the weight ratio of the carboxylated nanocellulose, carboxylic acid-polyethylene glycol-carboxylic acid, activation solution and triethylenetetramine in (1) is 0.6~1:0.2~0.6:15~25:0.1~0.2, and the activated carboxylated nanocellulose can be completely dissolved in the activation solution within this weight ratio range under the action of ultrasound.

[0007] Preferably, the outer diameter of the carboxylated nanocellulose in (1) is 4-10 nm and the length is 200 nm. Nanocellulose in this size range can be better adsorbed on the foam surface, enhancing the interfacial film strength of the foam. Shorter and thinner nanocellulose can be interwoven with montmorillonite sheets to form a more stable three-dimensional network structure, thereby improving the viscosity and temperature and shear resistance of the fracturing fluid. Nanocellulose of suitable size can interact with thickener molecules through hydrogen bonds, etc., further strengthening the network structure, improving the overall performance of the fracturing fluid, and meeting the fracturing construction requirements under different reservoir conditions.

[0008] Preferably, the activation solution in (1) is a phosphate buffer system activation solution, the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in the phosphate buffer system activation solution is 0.1 mol / L, and the concentration of N-hydroxysuccinimide is 0.05 mol / L. The reaction activity of the activated carboxylated nanocellulose is significantly enhanced, and its compatibility with other materials is improved.

[0009] Preferably, in the (2), the weight ratio of montmorillonite, hexadecyltrimethylammonium bromide and deionized water is 0.8-1.2:0.03-0.05:3-5.

[0010] Preferably, in the (3), the weight ratio of the intercalated modified montmorillonite, modified nanocellulose and deionized water is 1:0.8~1.2:8~12, and the modified nanocellulose can be completely dissolved in deionized water at this weight ratio. After the reaction is completed, during the process of cooling to room temperature, the intercalated modified montmorillonite suspended in the deionized water does not undergo obvious sedimentation, which indicates that the intercalated modified montmorillonite enters the cross-linked voids of the modified nanocellulose to form a new cross-linked structure. The modified nanocellulose serves as a skeleton to support the montmorillonite and inhibits the sedimentation of the montmorillonite.

[0011] Preferably, the foaming agent refers to lauryl betaine. The surface of carboxylated nanocellulose is negatively charged, so the electrical properties of the foaming agent have a significant effect on the initial volume and stability of the foam. Lauryl betaine contains both anionic and cationic groups, and when combined with carboxylated nanocellulose, it can provide good foam stability.

[0012] Preferably, the thickener is one of xanthan gum, carboxymethyl cellulose or hydrolyzed polyacrylamide.

[0013] Preferably, the cross-linking agent is one of triethanolamine borate, zirconium oxychloride or zirconium acetate.

[0014] Furthermore, the present invention also provides a method for preparing the novel environmentally friendly fracturing fluid, which specifically comprises the following steps: S1. Add the modified nanocellulose-montmorillonite composite powder to deionized water and stir at 200-300 rpm for 30-50 min to obtain a dispersion; S2. Add a foaming agent, a thickener, and a cross-linking agent to the dispersion obtained in S1, stir at 200-300 rpm for 2-4 hours, and then stir at a speed of 5000-10000 rpm on a high-speed emulsifier for 3-6 minutes to obtain a new environmentally friendly fracturing fluid.

[0015] Beneficial effects of the present invention: The present invention improves the foaming and foam stabilizing properties of the fracturing fluid by introducing modified nanocellulose-montmorillonite composite powder. The surface properties of nanocellulose are changed after specific modification, and it can be better adsorbed on the foam surface. Carboxylated nanocellulose is cross-linked with carboxylic acid-polyethylene glycol-carboxylic acid and triethylenetetramine during the modification process to form a cross-linked network structure, while the unique lamellar structure of montmorillonite is interwoven with the modified nanocellulose and embedded in the network of the modified nanocellulose. This structure enhances the interfacial film strength of the foam, effectively limits the diffusion of gas in the foam, and reduces the drainage rate of the foam, thereby improving the foaming efficiency and foam stabilizing ability, ensuring that a large amount of stable foam can be formed during fracturing construction, and providing a good carrier for carrying sand.

[0016] The novel environmentally friendly fracturing fluid of the present invention has good structural stability formed by the modified nanocellulose-montmorillonite composite powder and other components under different temperature environments. At lower temperatures, it can effectively limit molecular movement and maintain foam stability; at higher temperatures, the montmorillonite layer structure can support part of the network, slow down the speed of structural destruction, and ensure that the fracturing fluid can function stably under different reservoir temperature conditions.

[0017] The novel environmentally friendly fracturing fluid of the present invention uses deionized water as the main solvent, reducing the use of chemical solvents that are harmful to the environment. At the same time, the selected raw materials such as modified nanocellulose-deionized composite powder, foaming agent, thickener and cross-linking agent have good biodegradability and environmental friendliness on the basis of meeting the high performance requirements of the fracturing fluid, reducing the potential pollution risk of fracturing construction to the formation and the surrounding environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The half-life variation diagram of the fracturing fluids prepared by the preparation methods of Examples 1 to 3 and Comparative Examples 1 to 7 at different temperatures. DETAILED DESCRIPTION

[0019] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0020] Example 1: A specific method for preparing a new environmentally friendly fracturing fluid, comprising the following steps: (1) 5 g of carboxylated nanocellulose and 1.67 g of carboxylic acid-polyethylene glycol-carboxylic acid were co-dispersed in 125 g of an activation solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.05 M N-hydroxysuccinimide (pH = 5.5, phosphate buffer system), and ultrasonically treated for 1 h. Then, 0.83 g of triethylenetetramine was added, and the mixture was stirred at 55 ° C for 5 h under nitrogen protection. The mixture was freeze-dried, washed with n-hexane, and dried to obtain modified nanocellulose. (2) 5 g of montmorillonite, 0.19 g of hexadecyltrimethylammonium bromide and 18.75 g of deionized water were mixed, stirred at 50 °C for 1 h, filtered, washed and dried to obtain intercalated modified montmorillonite; (3) Add 4 g of the intercalated modified montmorillonite prepared in (2) to 32 g of deionized water, heat to 60 °C and stir for 2 h, then add 3.2 g of the modified nanocellulose obtained in (1), ultrasonicate for 20 min, and then stir for 6 h. After cooling to room temperature, freeze-dry, and grind through a 1000 mesh sieve to obtain a modified nanocellulose-montmorillonite composite powder.

[0021] (4) Add 4 g of the modified nanocellulose-montmorillonite composite powder prepared in (3) into 360 g of deionized water and stir at 200 rpm for 3 min to obtain a dispersion; (5) 0.4 g of lauryl betaine, 0.8 g of xanthan gum, and 2 g of triethanolamine borate were added to the dispersion obtained in (4), stirred at 200 rpm for 2 h, and then stirred at 5000 rpm for 3 min on a high-speed emulsifier to obtain a new environmentally friendly fracturing fluid.

[0022] Example 2: A specific method for preparing a new environmentally friendly fracturing fluid, comprising the following steps: (1) 10 g of carboxylated nanocellulose and 5 g of carboxylic acid-polyethylene glycol-carboxylic acid were co-dispersed in 250 g of an activation solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.05 M N-hydroxysuccinimide (pH = 5.5, phosphate buffer system), and ultrasonically treated for 2 h. 1.88 g of triethylenetetramine was then added. The mixture was stirred and reacted at 60 ° C for 6 h under nitrogen protection. The mixture was freeze-dried, washed with n-hexane, and dried to obtain modified nanocellulose. (2) 10 g of montmorillonite, 0.4 g of hexadecyltrimethylammonium bromide and 40 g of deionized water were mixed, stirred at 60 °C for 2 h, filtered, washed and dried to obtain intercalated modified montmorillonite; (3) Add 6 g of the intercalated modified montmorillonite obtained in (2) to 60 g of deionized water, heat to 70 °C and stir for 3 h, then add 6 g of modified nanocellulose obtained in (1), ultrasonicate for 25 min, and then stir for 9 h. After cooling to room temperature, freeze-dry, and grind through a 1200 mesh sieve to obtain a modified nanocellulose-montmorillonite composite powder.

[0023] (4) Add 8 g of the modified nanocellulose-montmorillonite composite powder prepared in (3) to 370 g of deionized water and stir at 250 rpm for 40 min to obtain a dispersion; (5) 0.8 g of lauryl betaine, 2 g of xanthan gum, and 4 g of triethanolamine borate were added to the dispersion obtained in (4), stirred at 250 rpm for 3 h, and then stirred at 7500 rpm for 5 min on a high-speed emulsifier to obtain a new environmentally friendly fracturing fluid.

[0024] Example 3: A specific preparation method of a new environmentally friendly fracturing fluid, comprising the following process: (1) 15 g of carboxylated nanocellulose and 9 g of carboxylic acid-polyethylene glycol-carboxylic acid were co-dispersed in 375 g of an activation solution containing 0.1 M 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 0.05 M N-hydroxysuccinimide (pH = 5.5, phosphate buffer system), and ultrasonically treated for 3 h. Then, 3 g of triethylenetetramine was added, and the mixture was stirred and reacted at 65 ° C for 7 h under nitrogen protection. The mixture was freeze-dried, washed with n-hexane, and dried to obtain modified nanocellulose. (2) 12 g of montmorillonite, 0.5 g of hexadecyltrimethylammonium bromide and 50 g of deionized water were mixed, stirred at 70 °C for 3 h, filtered, washed and dried to obtain intercalated modified montmorillonite; (3) Add 10 g of the intercalated modified montmorillonite obtained in (2) to 120 g of deionized water, heat to 80 °C and stir for 4 h, then add 12 g of the modified nanocellulose obtained in (1), ultrasonicate for 30 min, and then stir for 12 h. After cooling to room temperature, freeze-dry, and grind through a 1500 mesh sieve to obtain a modified nanocellulose-montmorillonite composite powder.

[0025] (4) Add 12 g of the modified nanocellulose-montmorillonite composite powder prepared in (3) into 380 g of deionized water and stir at 300 rpm for 50 min to obtain a dispersion; (5) 1.2 g of lauryl betaine, 3.2 g of xanthan gum, and 6 g of triethanolamine borate were added to the dispersion obtained in (4), stirred at 300 rpm for 4 h, and then stirred at 10,000 rpm for 6 min on a high-speed emulsifier to obtain a new environmentally friendly fracturing fluid.

[0026] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the carboxylated nanocellulose is not activated by EDC / NHS, and the specific process is as follows: A specific preparation method of a new environmentally friendly fracturing fluid includes the following process: (1) 10 g of carboxylated nanocellulose and 5 g of carboxylic acid-polyethylene glycol-carboxylic acid were co-dispersed in 250 g of phosphate-buffered deionized water (pH = 5.5), and ultrasonically treated for 2 h. Then, 1.88 g of triethylenetetramine was added, and the mixture was stirred at 60 ° C for 6 h under nitrogen protection. The mixture was freeze-dried, washed with n-hexane, and dried to obtain modified nanocellulose. (2) 10 g of montmorillonite, 0.4 g of hexadecyltrimethylammonium bromide and 40 g of deionized water were mixed, stirred at 60 °C for 2 h, filtered, washed and dried to obtain intercalated modified montmorillonite; (3) Add 6 g of the intercalated modified montmorillonite obtained in (2) to 60 g of deionized water, heat to 70 °C and stir for 3 h, then add 6 g of modified nanocellulose obtained in (1), ultrasonicate for 25 min, and then stir for 9 h. After cooling to room temperature, freeze-dry, and grind through a 1200 mesh sieve to obtain a modified nanocellulose-montmorillonite composite powder.

[0027] (4) Add 8 g of the modified nanocellulose-montmorillonite composite powder prepared in (3) to 370 g of deionized water and stir at 250 rpm for 40 min to obtain a dispersion; (5) 0.8 g of lauryl betaine, 2 g of xanthan gum, and 4 g of triethanolamine borate were added to the dispersion obtained in (4), stirred at 250 rpm for 3 h, and then stirred at 7500 rpm for 5 min on a high-speed emulsifier to obtain a new environmentally friendly fracturing fluid.

[0028] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that carboxylic acid-polyethylene glycol-carboxylic acid is not added when preparing the modified nanocellulose.

[0029] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that the carboxylated nanocellulose is directly composited with the intercalated modified montmorillonite without modification.

[0030] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that no montmorillonite is added during the preparation process.

[0031] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that no modified nanocellulose-montmorillonite composite powder is added.

[0032] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that the modified nanocellulose-montmorillonite composite powder is reduced to 3g.

[0033] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that the modified nanocellulose-montmorillonite composite powder is reduced to 5 g.

[0034] Performance Testing: 1. Foaming efficiency test: Take 100 ml of the dispersion before stirring in the high-speed emulsifier from each of Examples 1 to 3 and Comparative Examples 1 to 7, transfer to the high-speed emulsifier and stir rapidly at 8000 r / min for 5 min to prepare foam, then quickly pour the obtained foam into a 500 mL measuring cylinder and read the volume of the foam liquid. Foaming efficiency: , V0——initial liquid volume, V——formed foam volume, the experimental results are shown in Table 1.

[0035] 2. Half-life test: Take 100 ml of the dispersion before stirring in the high-speed emulsifier from Examples 1 to 3 and Comparative Examples 1 to 7, transfer them to the high-speed emulsifier and stir them rapidly at 8000 r / min for 5 min to prepare foam, then quickly pour the obtained foam into a 500 mL measuring cylinder, and record the time for 50 ml of liquid to precipitate from the foam in the measuring cylinder, which is the half-life of the fracturing fluid. The experimental results are shown in Table 1.

[0036] 3. Apparent viscosity test: The apparent viscosity of the fracturing fluids prepared in Examples 1 to 3 and Comparative Examples 1 to 7 was measured at room temperature using a NXS-11B rotational viscometer. The experimental results are shown in Table 1.

[0037] 4. Sand carrying performance test: Take the fracturing fluid prepared in Examples 1 to 3 and Comparative Examples 1 to 7, fill a 10 cm stoppered measuring cylinder, put ceramsite or glass beads with a diameter of 0.4 to 0.8 cm into the stoppered measuring cylinder, and measure the time taken for the ceramsite or glass beads to reach the bottom of the measuring cylinder, which is the sedimentation time. The experimental results are shown in Table 1.

[0038] 5. Water gel breaking time test: The fracturing fluids prepared in Examples 1 to 3 and Comparative Examples 1 to 7 were mixed with deionized water at a volume ratio of 1:3 at room temperature, shaken evenly, and the gel breaking phenomenon was observed and the gel breaking time was recorded. The experimental results are shown in Table 1.

[0039] 6. Stability test at different temperatures: record the change of half-life of the fracturing fluids prepared in Examples 1 to 3 and Comparative Examples 1 to 7 at different temperatures. The experimental results are as follows: Figure 1 shown.

[0040] Table 1 ;

[0041] Data Analysis: According to Table 1 and Figure 1 It can be seen from the data in that the fracturing fluids prepared by the preparation method of the present invention in Examples 1 to 3 have balanced properties, high foaming efficiency, strong foam stabilization ability, excellent sand carrying performance, and appropriate gel breaking time, especially at different temperatures. They all show good foam stabilization performance, among which Example 2 has the best performance. In terms of foaming efficiency, compared with Comparative Example 1, the carboxylated nanocellulose of Example 2 is activated by EDC / NHS, which enhances the reactivity of the nanocellulose and interacts better with the foaming agent lauryl betaine, so that it can be more effectively adsorbed on the foam surface, reduce surface tension, and promote the formation of foam, thereby improving the foaming efficiency; Comparative Example 2 does not add carboxylic acid-polyethylene glycol-carboxylic acid, and the carboxylated nanocellulose cannot form a firm network structure, and at the same time In the absence of polyethylene glycol, the formation and stability of the interfacial film are affected, the strength of the interfacial film is reduced, and it cannot effectively resist external interference. The foam is easy to break and it is difficult to form a large amount of stable foam, thereby reducing the foaming efficiency; in Example 3, the carboxylated nanocellulose is not modified, and its surface properties are not conducive to synergistic effect with the foaming agent, resulting in low foaming efficiency; in Example 4, no montmorillonite is added. The composite structure formed by montmorillonite and nanocellulose promotes foam stability. The lack of montmorillonite will reduce the foaming efficiency; in Example 5, no modified nanocellulose-montmorillonite composite powder is added, and the key foam stabilizing component is lost, and the foaming efficiency is greatly reduced; in Examples 6 and 7, the composite powder is reduced, the sites for stable foam are reduced, and the foaming efficiency is also affected.

[0042] In terms of half-life, comparative example 1 does not activate carboxylated nanocellulose, resulting in weak interaction with other ingredients, unstable foam interface film, and short half-life; comparative example 2 lacks carboxylic acid-polyethylene glycol-carboxylic acid, and cannot form a stable network structure to maintain the stability of the foam, and the half-life is shortened; comparative example 3 unmodified nanocellulose cannot effectively cooperate with other ingredients to stabilize the foam, and the half-life is short; comparative example 4 lacks montmorillonite, and the structure formed by the interweaving of montmorillonite sheets and nanocellulose is crucial to foam stability. Lack of it will reduce foam stability and shorten the half-life; comparative example 5 does not have composite powder, and basically cannot form stable foam, and the half-life is extremely short; comparative examples 6 and 7 have reduced composite powder amounts, and the ability to stabilize foam decreases, and the half-life is also shortened accordingly. In Example 2, the proportions of each component are appropriate, and the modified nanocellulose-montmorillonite composite powder, foaming agent, thickener, and cross-linking agent cooperate with each other to form a stable foam structure, so that the half-life is longer.

[0043] In terms of apparent viscosity, the carboxylated nanocellulose of suitable size in Example 2 interacts with the thickener molecules through hydrogen bonds and the like, strengthening the network structure; at the same time, the three-dimensional network structure formed by the modified nanocellulose-montmorillonite composite powder also helps to increase the viscosity. In Comparative Example 1, the unactivated nanocellulose interacts weakly with the thickener and cannot effectively enhance the viscosity; Comparative Example 2 lacks carboxylic acid-polyethylene glycol-carboxylic acid, which affects the formation of the composite structure and thus affects the viscosity enhancement; the unmodified nanocellulose in Comparative Example 3 cannot participate well in forming a high-viscosity network structure; Comparative Example 4 lacks montmorillonite, the network structure is incomplete, and the viscosity is low; Comparative Example 5 has no composite powder, and almost no effective viscosity-enhancing structure is formed, and the viscosity is extremely low; Comparative Examples 6 and 7 have insufficient composite powder, and the viscosity-enhancing effect is not as good as that of Example 2.

[0044] In terms of sand-carrying performance, i.e., sedimentation time, the stable three-dimensional network structure formed by the modified nanocellulose-montmorillonite composite powder in Example 2 and the system viscosity increased by the thickener can effectively hinder the sedimentation of ceramsite or glass beads. Comparative Examples 1 to 3 cannot form a good network structure to hinder sedimentation due to insufficient modification or activation of nanocellulose; Comparative Example 4 lacks montmorillonite, has an imperfect network structure, reduces sand-carrying capacity, and shortens sedimentation time; Comparative Example 5 has no composite powder, has almost no sand-carrying capacity, and has an extremely short sedimentation time; Comparative Examples 6 and 7 have reduced amounts of composite powder, weakened sand-carrying performance, and have a shorter sedimentation time than Example 2.

[0045] In terms of gel breaking time, although the modified nanocellulose produces a cross-linked structure, it will extend the gel breaking time of the fracturing fluid, but in the embodiment, carboxylic acid-polyethylene glycol-carboxylic acid is used as a flexible cross-linking agent, and the amino group of nanocellulose and triethylenetetramine reacts to form a cross-linked network, and carboxylic acid-polyethylene glycol-carboxylic acid provides a large steric hindrance, so that the degree of cross-linking is controlled, and the formed network provides stability and allows reversible dissociation under water or shear force, thereby avoiding the difficulty of gel breaking caused by excessive cross-linking, and the lamellar structure of montmorillonite is dispersed in the nanocellulose network to form a physical support framework, reducing the dependence on chemical cross-linking, and when breaking the gel, the water molecule penetration between the montmorillonite layers can accelerate the disintegration of the network without completely destroying the chemical bonds, and on the basis of ensuring the high foaming efficiency and sand carrying performance of the fracturing fluid, the gel breaking time is controlled within a reasonable range. In comparative example 2, the modified nanocellulose does not add the key component of carboxylic acid-polyethylene glycol-carboxylic acid, and the degree of cross-linking of nanocellulose is not well controlled, and the cross-linking is relatively dense, resulting in difficulty in gel breaking of the fracturing fluid.

[0046] In terms of stability at different temperatures, the half-life of the fracturing fluid prepared by adding montmorillonite is generally very stable or even improved at lower temperatures (20~40℃). At higher temperatures (40~90℃), the decrease in half-life is also relatively slow compared to the fracturing fluid without montmorillonite. This may be because montmorillonite has a special lamellar structure. After adding montmorillonite, it can interweave with modified nanocellulose to form a stable three-dimensional network structure at a lower temperature. This network structure is like a framework that can effectively limit the movement of liquid molecules and reduce the drainage rate of the foam, thereby making the foam more stable and the half-life can be kept stable or even increased; at the same time, although high temperature will affect the stability of the system to a certain extent, the network structure formed by montmorillonite and modified nanocellulose can still maintain integrity to a certain extent. The lamellar structure of montmorillonite has good thermal stability and can support part of the network to prevent it from completely collapsing. The system without montmorillonite lacks this support structure at high temperatures, and the network structure quickly disintegrates, resulting in a significant decrease in stability; finally, from Example 2 and Comparative Example 6~7, it can be seen that the amount of composite powder added also directly affects the stability of the fracturing fluid at different temperatures. This may be because in Example 2, the amount of modified nanocellulose-montmorillonite composite powder added is appropriate, and the nanocellulose and montmorillonite are fully intertwined. Under low temperature conditions, this composite structure can effectively limit molecular thermal motion, reduce foam drainage and gas diffusion, and the network formed by the montmorillonite layer and the nanocellulose is like a "molecular fence", which fixes the liquid and gas in a specific area and maintains the stability of the foam. However, in comparative examples 6~7, the amount of composite powder added is insufficient, the network structure is sparse, and the molecular motion cannot be effectively restricted, resulting in a decrease in stability.

[0047] It should be understood by those skilled in the art that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A new type of environmentally friendly fracturing fluid, characterized in that: The invention comprises the following raw materials in parts by weight: deionized water: 90-95 parts, modified nanocellulose-montmorillonite composite powder: 1-3 parts, foaming agent: 0.1-0.3 parts, thickener: 0.2-0.8 parts, crosslinking agent: 0.5-1.5 parts; The specific preparation method of the modified nanocellulose-montmorillonite composite powder is as follows: (1) Dispersing carboxylated nanocellulose and carboxylic acid-polyethylene glycol-carboxylic acid in an activation solution, ultrasonically treating for 1 to 3 hours, adding triethylenetetramine, stirring and reacting at 55 to 65°C for 5 to 7 hours under nitrogen protection, freeze-drying, washing, and drying to obtain modified nanocellulose; (2) Mixing montmorillonite, hexadecyltrimethylammonium bromide and deionized water, maintaining the temperature at 50-70°C and stirring for 1-3 hours, filtering, washing and drying to obtain intercalated modified montmorillonite; (3) The intercalated modified montmorillonite prepared in (2) is added to deionized water, heated to 60-80°C and stirred for 2-4 hours, and then the modified nanocellulose obtained in (1) is added, ultrasonicated for 20-30 minutes, and then stirred for 6-12 hours. After cooling to room temperature, the modified nanocellulose-montmorillonite composite powder is obtained by freeze-drying and grinding through a 1000-1500 mesh sieve.

2. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The weight ratio of carboxylated nanocellulose, carboxylic acid-polyethylene glycol-carboxylic acid, activation solution and triethylenetetramine in (1) is 0.6~1:0.2~0.6:15~25:0.1~0.

2.

3. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The outer diameter of the carboxylated nanocellulose in (1) is 4-10 nm and the length is 200 nm.

4. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The activation solution in (1) is a phosphate buffer system activation solution, in which the concentration of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 0.1 mol / L, the concentration of N-hydroxysuccinimide is 0.05 mol / L, and the pH is 5.

5.

5. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The weight ratio of montmorillonite, hexadecyltrimethylammonium bromide and deionized water in (2) is 0.8-1.2:0.03-0.05:3-5.

6. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The weight ratio of the intercalated modified montmorillonite, modified nanocellulose and deionized water in (3) is 1:0.8~1.2:8~12.

7. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The foaming agent refers to lauryl betaine.

8. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The thickener is one of xanthan gum, carboxymethyl cellulose or hydrolyzed polyacrylamide.

9. The novel environmentally friendly fracturing fluid according to claim 1, characterized in that: The cross-linking agent is one of triethanolamine borate, zirconium oxychloride or zirconium acetate.

10. The method for preparing the novel environmentally friendly fracturing fluid according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Add the modified nanocellulose-montmorillonite composite powder to deionized water and stir at 200-300 rpm for 30-50 min to obtain a dispersion; S2. Add a foaming agent, a thickener, and a cross-linking agent to the dispersion obtained in S1, stir at 200-300 rpm for 2-4 hours, and then stir at a speed of 5000-10000 rpm on a high-speed emulsifier for 3-6 minutes to obtain a new environmentally friendly fracturing fluid.

Citation Information

Patent Citations

  • Rapidly hydrated liquid guanidine gum and fracturing base fluid containing same

    CN103865514A

  • Nano coating fiber active fracturing fluid

    CN104498019A

  • Nano-composite fracturing fluid as well as preparation method and application thereof

    CN107325805A

  • Modified nano-montmorillonite and preparation method thereof, polymer fracturing fluid synergist and preparation method and application of polymer fracturing fluid synergist

    CN114395388A

  • Temperature-resistant and salt-resistant composite oil displacement agent and preparation method thereof

    CN116042201A

Cited By

  • Emulsion modified fracturing fluid and preparation method thereof

    CN120098632A